Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s12070-013-0692-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Endoscopic Septoplasty Versus Conventional Septoplasty

Abstract: Nasal obstruction due to deviated nasal septum is a common problem encountered by otolaryngologists. A variety of surgical procedures have been tried in the treatment of the same. This study was conducted to evaluate the outcomes and complications of endoscopic and conventional septoplasty. This is a prospective, randomized study. Fifty patients with symptomatic deviated nasal septum were included in the study, 25 of them underwent conventional septoplasty and the rest underwent endoscopic septoplasty. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 11 publications
4
37
2
3
Order By: Relevance
“…Other studies have reported significantly less number of septal perforations in the endoscopic group as compared to the conventional septoplasty group. [7][8][9] Park et al in their study conducted in 1998 observed that the synechiae formation was significantly less in patients of endoscopic septoplasty group as compared to conventional group; similar results were found in the study conducted by Jain et al and Gulati et al 7,16,17 This is in agreement with our study where the synechia formation was observed in 20% patients with conventional septoplasty and only in 2% patients with endoscopic septoplasty.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Other studies have reported significantly less number of septal perforations in the endoscopic group as compared to the conventional septoplasty group. [7][8][9] Park et al in their study conducted in 1998 observed that the synechiae formation was significantly less in patients of endoscopic septoplasty group as compared to conventional group; similar results were found in the study conducted by Jain et al and Gulati et al 7,16,17 This is in agreement with our study where the synechia formation was observed in 20% patients with conventional septoplasty and only in 2% patients with endoscopic septoplasty.…”
Section: Discussionsupporting
confidence: 91%
“…12 In a study by Sathyaki et al, headache persisted in 2 of the 10 patients in conventional septoplasty group while none of the patients in the endoscopic septoplasty group complained of headache. 9 In our study headache persisted in 3 (20%) of the 15 patients' with conventional septoplasty and in 2(8%) of the 25 patients with endoscopic septoplasty.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations